Technological breakthrough in criminalistics and forensic examination: new horizons - Avdeeva, Galina (Archives of Criminology and Forensic Sciences, 2025)
This scientific article focuses on exploring the directions for the application of the latest technologies in criminalistics and forensic examination in Ukraine and other countries. Thanks to global digitalization, open access to scientific publications and research data has become available to scientists from most countries worldwide. Open science has emerged as a new reality in the research activities of the world’s leading scientific communities, including Ukraine. This creates opportunities for a significant technological breakthrough in the development of criminalistics and forensic examination. Based on the study and analysis of scientific and other sources from Ukraine and other countries, the following open-access digital forensic platforms available to law enforcement agencies were identified and analyzed: the Automated Fingerprint Identification System (AFIS); facial recognition systems Clearview AI (USA) and SmartFace (Slovakia); the BigDataPeople system (Ukraine) for collecting information about individuals using opensource data; the BalScan ballistic identification system (Czech Republic); the databases of cold steel and firearms maintained by the Netherlands Forensic Institute; the IBIS system for automated firearm and toolmark identification based on 3D trace imaging; the free ChemSpider database of medicines and bioproducts (United Kingdom); the ABIS biometric identification management system (Slovakia), which utilizes palm prints, iris scans, and facial features, among others. The latest forensic methods for evidence examination, described in open sources and considered promising for use in Ukraine, have been identified. These include: studying narcotic materials, explosives, chemical, and biological substances at the atomic and molecular levels (nanotechnology); identifying individuals and determining their age based on the complete set of proteins produced by the human body; determining the time of death based on various markers (blood pH, cholesterol, sodium, potassium, etc.); determining human characteristics (age, skin color, eye and hair color) through DNA analysis, and more. The integration of Ukrainian forensic knowledge into European and global open science systems requires not only adherence to their standards and principles but also the unification and standardization of metadata exchange protocols, including their content and format.